ChemInform Abstract: Synthesis of Stable Aromatic and Heteroaromatic Sulfonyl‐Amidoximes and Evaluation of Their Antioxidant and Lipid Peroxidation Activity. Issue 47 (6th November 2014) - Doulou, Ismini; Kontogiorgis, Christos; Koumbis, Alexandros E.; Evgenidou, Eleni; Hadjipavlou‐Litina, Dimitra; Fylaktakidou, Konstantina C.
Abstract Evaluation of antioxidant activities shows that most of the compounds (III) synthesized (17 out of 28 compounds) highly compete with DMSO for hydroxyl radicals, while five of them, e.g. compounds (IIIa), (IIId) and (IIIg), inhibit lipid peroxidation.